Stress intensity factors numerical calculations for two penny shaped cracks in the elastic solid. (May 2020) - Đukić, D.; Grbović, A.; Kastratović, G.; Vidanović, N.; Sedmak, A.
Highlights: MSD is being redefined because of current tendency to modify existing aircraft. Numerical methods and real-time condition monitoring: two completely opposite trends. Assessment of numerical methods was performed through comparison of the SIFs results. Overall deviation within obtained and referent results was quite acceptable. State of the art numerical methods SMART and XFEM showed minimal deviation. Abstract: In the face of enormous costs of developing new aircraft, high fuel prices, increasingly demanding environmental standards, harsh economic race and the fight against competing manufacturers, today's aviation is adapting not by producing brand new, more advanced aircraft, but through modifying existing ones by incorporating new more energy efficient engines, in accordance with today's leading criterion that requires minimal fuel consumption, enabling at the same time the longest possible range. The structure of these "new" aircraft is metallic and almost identical as it has been for decades, but now with the new requirement that its service life has to be extended, as long as it is economically justified. In such environment, it is clear that one of the leading tasks is to have the best possible assessment of the negative impact of the mechanism of Multiple Site Damage (MSD), which represents an introduction to the phenomenon of Widespread Fatigue Damage (WFD), the most insidious degradation mechanism of a metallic structure, whose significance was supposed to be diminished in recent decades with accelerated growth in the application of the composite structures. In line with the aforementioned trends, this paper aims to evaluate to what extent today's numerical methods are capable to contribute to the assessment of behavior of such phenomena and which of the proposed approaches could be used for investigating of the fracture problems, both accurately and efficiently. This assignment was conducted through numerical computations of stress intensity factors (SIFs) for two penny shaped cracks in elastic solid estimated by the methods that the authors of this paper consider to be the most relevant in the last few years.